2003
DOI: 10.1117/12.497665
|View full text |Cite
|
Sign up to set email alerts
|

<title>Evaluation of pointing techniques for ray casting selection in virtual environments</title>

Abstract: Various techniques for object selection in virtual environments have been proposed over the years. Among them, the virtual pointer or ray-casting is one of the most popular method for object selection because it is easy and intuitive to use and allows the user to select objects that are far away. Variants of the virtual pointer metaphor include the Aperture [5], Flashlight [3], and Image plane method [fl as categorized as such by [10]. In a monoscopic environment, these methods are essentially 2D interaction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 10 publications
2
24
1
2
Order By: Relevance
“…For 3D data, raycasting selection techniques (e. g., [1,18,25,36]) are common in virtual environments that range from desktop VR to CAVEs; for true volumetric displays similar techniques are used [10]. Raycasting is frequently employed because it can be operated at a distance, is fast, and is easily understandable [21].…”
Section: Related Workmentioning
confidence: 99%
“…For 3D data, raycasting selection techniques (e. g., [1,18,25,36]) are common in virtual environments that range from desktop VR to CAVEs; for true volumetric displays similar techniques are used [10]. Raycasting is frequently employed because it can be operated at a distance, is fast, and is easily understandable [21].…”
Section: Related Workmentioning
confidence: 99%
“…The results of the Borg Scale in our experiment indeed showed that participants reported more muscle fatigue with gaze-directed than with hand-directed pointing. The influence of muscle fatigue on the accuracy of hand placement has been supported by Lee et al (2003). Additionally, Bowman et al (2002) mentioned that hand tremors may influence the precision of target selection with the ray casting method and termed this phenomenon the "Heisenberg effect".…”
Section: Performancementioning
confidence: 96%
“…The muscle fatigue would have reduced the precision and speed of the pointing performance. Several previous studies (Bowman et al, 2002;Gallo and Minutolo, 2012;Lee et al, 2003) have pointed out the problem of tremors in precise pointing tasks. The results of the Borg Scale in our experiment indeed showed that participants reported more muscle fatigue with gaze-directed than with hand-directed pointing.…”
Section: Performancementioning
confidence: 99%
“…Ray-casting is scalable, however computationally expensive 11 , but its simplicity lends its application well for applications ranging from virtual navigation to large intelligent ground vehicles such as with the DARPA Urban Challenge 12 . A complete discussion of all of the vision applications of ray-casting is out of the scope of this paper; however, a few of the vision applications where ray-casting algorithms have been applied include navigation of virtual environments such as with computer games 13 , pointer techniques 14 and medical applications where CT or MRI scans provide the virtual landscape 15 to navigating actual 3D environments such as with intelligent ground vehicles 2,12,16 . In robotics, ray-casting algorithms are typically used like a virtual LIDAR scanning the sensor collected information such that either a 2D or 3D map can be generated from which navigation decisions can be made 2, 16 ; in our application, however, we have applied ray-casting to find the openings in the sensory data where our robot can most easily pass through the obstacles.…”
Section: Vision Processingmentioning
confidence: 99%